Motiv trikotnika s podaljški na glinenem posodju v pozni bronasti in zgodnji železni dobi. Razmislek o njegovi okrasni in simbolni vrednostiThe Motif of the Triangle with Extensions on the Ceramic Vessels of the Late Bronze and Early Iron Age. The Reflection towards Its Ornamental and Symbolic Value - Škvor Jernejčič, Brina (Studia mythologica Slavica, 2011)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The following article is an attempt at interpretation of the so-called triangle with extensions that appears as an ornament on prehistoric ceramic vessels (end of the 2nd and beginning of the 1st millennium BC). According to archaeological and further ethnological analogies within Eurasian territory, we presume that the ornament–symbol in question not only presents a feminine figure, as discussed in preceding studies, but can also be read as a house, home, oven or a posture of crossed arms. Furthermore, it seems that this sign has a symbolical function to protect and to shelter.